Pemberdayaan Masyarakat Desa melalui Literasi Akuntansi Digital pada Program Catat Uang Desa dengan Cerdas - Daud, Maiercherinra; Sanda Sip, Afian Dezi; Sambo, Eva Marin; Suriyadi Nur; Ana Rusmardiana (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2025)
This community service program aims to improve the literacy and digital accounting skills of residents of Kalukuang Village, Takalar Regency, through the "Record Village Money Smart" program. The activity was carried out in three stages, namely socialization on the importance of accountable financial records, education on the use of Android-based and desktop-based digital accounting applications, and discussions. The evaluation methods used include direct observation, pre-test and post-test and evaluation questionnaires to measure participants' understanding. The results showed that 83.5% of participants were able to operate the application independently, 91% felt that the training was very relevant and easy to follow, and 78% began to implement the application in recording real village transactions. This activity has a positive impact on recording efficiency, increased transparency, and strengthened village financial accountability. The program is recommended to be replicated in other villages with an adaptive local approach.